Desenvolvimento de vidro metálico de elevada resistência à corrosão e ao desgaste utilizando ferro-gusa como precursor - Martins, Caio Lucas Gueiros Pedrosa (Universidade Federal de São Carlos, 2023)
Metallic glasses exhibit exceptional properties such as high mechanical strength, thermal stability, and excellent magnetic properties. In this study, our aim was to develop a high corrosion and wear-resistant metallic glass from pig iron, a ferrous alloy with high impurity content and low added value. Two alloys, Fe68Cr8(C,B)24 and Fe62Cr8Nb4Mo4(C,B)22, composed of pig iron and commercially pure elements, were produced using an electric arc furnace. The alloys were processed via melt-spinning to obtain metallic ribbons and through centrifugal casting into copper molds to produce 1 mm thick plates. Characterization of the alloys involved X-ray diffraction, exploratory scanning calorimetry, scanning electron microscopy, transmission electron microscopy, Vickers microhardness, electrochemical, and tribological tests. While the alloys processed by centrifugal casting did not vitrify due to slower cooling rates, they exhibited high hardness, surpassing 1000 HV, resulting in significant wear resistance. On the other hand, the Fe62Cr8Nb4Mo4(C,B)22 alloy produced by melt-spinning successfully formed a fully vitrified structure. This vitreous nature was confirmed through X-ray diffraction, including synchrotron radiation, and transmission electron microscopy. The glass transition temperature was approximately 553°C, with crystallization initiation at 574°C and a supercooled liquid region of 21°C. The Fe62Cr8Nb4Mo4(C,B)22 alloy demonstrated higher hardness compared to pig iron (1070 vs. 666 HV0.1, respectively) and greater stability in chloride-rich environments than the stainless steel 444, as evaluated by the passivation window before pitting corrosion (1253 vs. 738 mV, respectively) and easiness of re-passivation during the reverse scan. These results contribute to the production of resistant, hard, and cost-effective metallic glass alloys capable of meeting demanding applications.
Development of metallic glass with high resistance to corrosion and wear using pig iron as a precursor
Keywords: Ferro-gusa; Vidro metálico; Corrosão; Desgaste; Pig iron; Metallic glass; Corrosion; Wear; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA